2002
DOI: 10.1088/0953-8984/14/8/335
|View full text |Cite
|
Sign up to set email alerts
|

Local structural orders in nanostructured Al2O3prepared by high-energy ball milling

Abstract: Nanostructured Al 2 O 3 powders were prepared by high-energy ball milling of corundum. Both the solid state nuclear magnetic resonance spectra of the Al 3+ ions and the solid state electron paramagnetic resonance spectra of incorporated Fe 3+ ions are governed by noticeable spectral changes dependent on the duration of the mechanical treatment. The quadrupolar parameters of the 27 Al nuclei and the zero-field splitting parameters of the Fe 3+ ions as well as their statistical distributions were determined as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 23 publications
6
69
0
1
Order By: Relevance
“…These results indicate that the reduction in the intensity of the ball milled samples is due to an increase in the disorder of the samples with increased milling time. This is in agreement with results for other ball milled nanocrystalline oxides such as ZrO 2 , [47] LiNbO 3 [44] and Al 2 O 3 , [43] where the disorder has been shown to increase with the fraction of amorphous material.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…These results indicate that the reduction in the intensity of the ball milled samples is due to an increase in the disorder of the samples with increased milling time. This is in agreement with results for other ball milled nanocrystalline oxides such as ZrO 2 , [47] LiNbO 3 [44] and Al 2 O 3 , [43] where the disorder has been shown to increase with the fraction of amorphous material.…”
supporting
confidence: 92%
“…[32][33][34] Generally, for nanocrystalline metal oxides, carefully prepared by sol-gel routes, there is now reliable EXAFS evidence for the nanocrystals having similar grain boundaries to those in the bulk materials, with similar levels of static and dynamic disorder. [36][37][38][39][40][41][42] High-energy ball milling is widely used for the preparation of nanocrystalline samples, [17,[42][43][44][45][46][47] however, it is emerging that the microstructure obtained is very different to that obtained using other methods. For example, a study of 13 nm corundum, Al 2 O 3 , prepared by ball milling, revealed a significant fraction of amorphous material in the sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this measurement temperature the differences can only be due to differences in the level of static disorder in the samples. We interpret this as the formation of significant levels of amorphous material in the ball-milled samples, a feature of this method of sample preparation [44,73,75].…”
Section: Zirconiamentioning
confidence: 91%
“…This has to be minimized by choosing appropriate materials for the milling vial and balls, respectively. A further disadvantage is that the milling can produce amorphous debris, to the extent that recent work on ball milled Al 2 O 3 indicated that the sample consisted of nanocrystalline grains embedded in amorphous material [44].…”
Section: Sample Preparationmentioning
confidence: 99%